ANALYSIS OF MORBIDITY AND MORTALITY RATE IN BOVINE UNDER VILLAGE CONDITIONS OF UTTAR PRADESH - SAURABH UTTAM; B. SINGH; J. K. CHAUDHARY; S. BASSAN; SUNEEL KUMAR; NEHA GUPTA (The Bioscan, 2015)
The present study was carried out to analyse the factors associated with morbidity and mortality rate in bovine under village conditions of Uttar Pradesh using suitable statistical techniques. A total of 480 bovine owners were randomly selected from Allahabad division of Uttar Pradesh, constitute the ultimate sample for the study. The sampling scheme followed in the present study was multistage random sampling with equal probability without replacement. Morbidity and mortality data were collected from all selected bovine owners for period of one year (January 2013 to December 2013). Overall morbidity rate was 32.46% in bovine, higher in buffalo 33.17% than 30.35% in cattle and overall mortality rate was 5.03% in bovine, higher in buffalo 5.21% than 4.49% in cattle. The diseases were classified into seven categories of which reproductive diseases were more prominent in incidence having highest morbidity rate 8.75% followed by specific diseases 5.59% and major causes of mortality in bovine were reproductive diseases 1.43% followed by digestive diseases 0.99%.